2018
DOI: 10.2147/prom.s157213
|View full text |Cite
|
Sign up to set email alerts
|

The Relational Aspects of Care Questionnaire: item reduction and scoring using inpatient and accident and emergency data in England

Abstract: PurposeThe Relational Aspects of Care Questionnaire (RAC-Q) is an electronic instrument which has been developed to assess staff’s interactions with patients when delivering relational care to inpatients and those accessing accident and emergency (A&E) services. The aim of this study was to reduce the number of questionnaire items and explore scoring methods for “not applicable” response options.Patients and methodsParticipants (n=3928) were inpatients or A&E attendees across six participating hospital trusts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Using published formulae by Hayes and Moulton, 16 we calculated our patient participant sample size based on an estimate of the minimum clinically important difference for the QPP of 0.2 and the typical within-unit standard deviation (0.6), supplied by the measure developers and an intraclass correlation coefficient (ICC) of 0.02. We have examined a number of potential scenarios, taking into account different cluster sizes and different between-cluster SD values informed by between-country differences on measures, estimated to provide 90% and 80% power.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…Using published formulae by Hayes and Moulton, 16 we calculated our patient participant sample size based on an estimate of the minimum clinically important difference for the QPP of 0.2 and the typical within-unit standard deviation (0.6), supplied by the measure developers and an intraclass correlation coefficient (ICC) of 0.02. We have examined a number of potential scenarios, taking into account different cluster sizes and different between-cluster SD values informed by between-country differences on measures, estimated to provide 90% and 80% power.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…MOH received over five thousand official complaints each year, and at least a quarter of the complaints were related to poor service quality [ 8 ]. However, contrary to the common belief that the lack of compassionate care is due to healthcare worker’s (HCW) weakness and ignorance, evidence showed that patients’ characteristics and the care environment considerably affect patients’ perspectives on the compassionate care provided [ 9 , 10 , 11 , 12 ]. As long as these factors are not recognized, the quality of our image of healthcare will be jeopardized.…”
Section: Introductionmentioning
confidence: 99%
“…It measures the relational aspect of care across 22 themes [ 11 ]. The completion of the survey requires a mean time of 8.5 min, with a standard deviation of 9.9 min [ 12 ]. The original RAC-Q was administered digitally, and the responses were captured in near real time.…”
Section: Introductionmentioning
confidence: 99%
“…As the first step in screening, instruments capturing self-reported symptoms reduce the cost and time requirements of formal clinical diagnostic interviews [15]. The desirability of shorter screening procedures is threefold-first, brief screening instruments reduce the participant response burden; second, shorter instruments may be more readily used in resource-constrained settings because of administration and cost efficiencies; and third, shorter instruments may result in fewer missing responses and thus reductions in the risk of invalidation due to missingness [16]. Overall, ideal screening instruments in humanitarian crises are (1) self-reported or administered by trained non-medical health workers [2], and (2) responsiveness to change [17], with (3) demonstrated acceptable response rate, reliability, and validity in displaced populations [14], (4) and a minimal response burden [16].…”
Section: Introductionmentioning
confidence: 99%